Vicinal diaryl substituted heterocycles : a gold mine for the discovery of novel therapeutic agents - Yadav, M. R.; Murumkar, P. R.; Ghuge, R. B. (Elsevier, 2018)
Vicinal Diaryl-Substituted Heterocycles: A Gold Mine for the Discovery of Novel Therapeutic Agents draws together all of the key information about these compounds in one place for the first time. Following an informative overview of the importance of these structures to the discovery of potential therapeutic agents, the text goes on to outline the main compound types, with each chapter focusing on the activities of a different structure. Designed to support researchers by consolidating this important information in a single, practical guide, the authors hope to encourage further advancement and development in the discovery of novel therapeutic agents. As flexible building blocks for the production of novel compounds, vicinal diaryl-substituted heterocycles are a rich source of leads for the development of new drugs. Their adaptability means that they can be used to produce structures with a broad range of attractive characteristics, and a large number of vicinal diaryl-substituted heterocyclic compounds have already been synthesized and investigated by medicinal chemists as promising lead molecules.